A novel, simple and rapid route to the synthesis of boron cabonitride nanosheets: combustive gaseous unfolding - Maisam Jalaly (Nature Portfolio, 2017)
Abstract The ternary compound boron carbonitride (BCN) was synthesized in the form of few-layer nanosheets through a mechanically induced self-sustaining reaction (MSR). Magnesium was used to reduce boron trioxide in the presence of melamine in a combustive manner. The process to form the nanostructured material was very rapid (less than 40 min). The prepared powder was investigated by various techniques such as X-ray diffraction (XRD), Fourier Transform infrared (FTIR), Micro-Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), high-resolution transmission electron microscopy (HRTEM), and electron energy loss spectroscopy (EELS). The thermal stability and the optical behavior of the BCN nanosheets were also studied by thermal analysis and UV-vis spectroscopy, respectively. The formation mechanism of the nanosheet morphology was described in detail.